Clinical and Prognostic Value of Depressive Symptoms and N-Terminal Pro–B-Type Natriuretic Peptide in Patients With Eisenmenger Syndrome. Issue 7 (September 2015) - Moon, Ju Ryoung; Kang, Dae Ryong; Song, Jinyoung; Huh, June; Kang, I-Seok; Chang, Sung A.; Park, Seung Woo; Lee, Heung Jae
ABSTRACT Objectives Eisenmenger syndrome (ES) is commonly associated with depressive symptoms and elevated N-terminal pro–B-type natriuretic peptide (NT-proBNP). We investigated the predictive value of depressive symptoms and NTproBNP levels for long-term outcomes in patients with ES. Methods Blood was drawn to measure NT-proBNP, and depressive symptoms were measured using the Korean version of the Beck Depression Inventory (BDI) in an outpatient clinic sample of 64 patients with ES (67% female; median age = 41.5 years [range, 21.0–74.8 years]). Cardiac events (hospitalization, emergency department visits, and cardiac death) were monitored during 3 years of follow-up. Results During the follow-up period, 15 (23.4%) patients experienced a cardiac event. The combination of depressive symptoms and NT-proBNP levels better predicted future cardiac events than either variable alone. Patients with NT-proBNP > 510 pg/ml and a total BDI score > 10 had a 9.6 times higher risk for cardiac events than did patients with NT-proBNP ⩽ 510 pg/ml or total BDI score ⩽ 10 (p < .001). Conclusions Depressive symptoms and NT-proBNP levels are both associated with adverse clinical outcomes in ES.